Kualitas dan Kuantitas Ketersediaan Sumber Air Minum Sungai Cikaduen Kecamatan Taktakan Provinsi Banten - Ade Ariesmayana; Frebhika Sri Puji Pangesti (Fakultas Teknik, 2023)
The provision of drinking water is one of the basic needs and socio-economic rights of the community that must be fulfilled by the Government. The rapid development of housing in Taktakan Sub-district, the main and supporting infrastructure needs to be properly prepared. One infrastructure that is prioritised is the drinking water supply system. The research used the observation method to see the condition of the Cikaduen River, and laboratory tests to analyse raw water sources with physical, chemical, and microbiological parameters. This research was conducted from December 2021-March 2022. The purpose of this research is to prepare a drinking water supply system planning in Taktakan District. Based on the results of laboratory tests, physical parameters such as temperature, TDS, and TSS all meet the Class I Water Quality Standards PP 22 of 2021, while for chemical parameters some parameters exceed the quality standard threshold such as BOD5, COD, DO, Fluoride, Copper. Microbiology meets the Water Quality Standard. The instantaneous discharge of Cikaduen River is 518 l/s. From the results of hydrological analysis, it is known that the availability of water to serve the population in Taktakan is 60 ltr/s. Based on the availability of water from the results of the analysis using FJ Mock, the Cikaduen River is suitable to be used as a source of raw water.